Time‐Domain Reflectometry Measurements and Modeling of Firn Meltwater Infiltration at DYE‐2, Greenland. Issue 10 (6th October 2021) - Samimi, S.; Marshall, S. J.; Vandecrux, B.; MacFerrin, M.
Abstract: Surface meltwater can be retained in an ice sheet if it infiltrates the firn and refreezes. This is an important mass balance process for the Greenland Ice Sheet, reducing meltwater runoff and associated sea‐level rise. The processes of meltwater infiltration and refreezing are not fully understood, however, and remain difficult to monitor remotely. We deployed vertical arrays of thermistors and time‐domain reflectometry (TDR) probes to 4‐m depth in the firn to continuously monitor meltwater infiltration and refreezing processes at DYE‐2, Greenland. The observations provide a detailed picture of the coupled thermal and hydrological evolution of the firn through the 2016 melt season, including estimates of firn water content. The thaw and wetting fronts reached a maximum depth of 1.8 m, with meltwater infiltration concentrated in four main pulses of melting and subsurface warming that reached progressively deeper into the firn. The observations were used to constrain a coupled model of firn thermodynamics and hydrology, which was then run over the period 1950–2020, driven by meteorological forcing from GC‐Net station data and ERA5 climate reanalyses. Model results suggest that decadal‐scale firn evolution at DYE‐2 is strongly influenced by extreme melt seasons such as those of 1968, 2012, and 2019, when meltwater infiltration reached depths of 6–7 m. Extreme melt years drive increases in firn temperature, ice content, and density, reducing firn meltwater retention capacity. Such processes are likely to govern future meltwater retention as the percolation zone extends to higher elevations in Greenland in the coming decades. Plain Language Summary: On polar ice sheets, the vast majority of surface meltwater either runs off to the ocean or is refrozen in porous layers of snow and firn. These processes are important to understand across the Greenland Ice Sheet because they influence how much meltwater contributes to sea level rise versus being retained within the ice sheet in any given year. However, the subsurface nature of meltwater percolation and refreezing makes these processes difficult to accurately monitor, and the conditions that control meltwater retention are also evolving with the changing climate. In the spring of 2016, we deployed a novel array of buried temperature and wetness sensors in the snow and firn at the DYE‐2 site in Greenland to monitor the infiltration and refreezing of meltwater in firn, as well as a meteorological station at the surface to collect weather and radiation data. The station measured the evolution of firn structure and temperature over a full annual cycle of melting and refreezing. We used the field measurements to constrain a computer model that simulates firn density, melt, and refreezing processes at the same location in Greenland from 1950 through 2020, based upon historical climate reconstructions. We find that, while large summer melt events appear periodically in the long‐term record, including a notable melt summer in 1968, recent extreme melt events at DYE‐2 in 2012 and 2019 are altering subsurface firn properties in ways that will reduce meltwater retention capacity in Greenland's percolation zone in a warming Arctic climate. Key Points: Time‐domain reflectometry provided continuous monitoring of firn liquid water content and meltwater infiltration through a melt season A simple coupled model of firn thermodynamics and hydrology reproduces the observed evolution of the firn thawing and wetting fronts Modeling from 1950 to 2020 indicates that extreme melt seasons govern trends in firn temperature, density, and ice content at DYE‐2